Efibula cremea sp. nov. (Irpicaceae, Polyporales), a coriaceous fungus from Yunnan Province, China - Li, Qi; Zhang, Yuewei; Zhao, Changlin; Li, Wenli (Phytotaxa, 2025)
A new species, Efibula cremea, found in Yunnan Province, China, is described and illustrated based on morphological and phylogenetic analyses. Efibula cremea is characterized by its coriaceous basidiomata with a grandinioid hymenial surface, a monomitic hyphal system with generative hyphae bearing simple-septate, and ellipsoid basidiospores measuring 4.7–5.7 × 3.3–4 µm. Sequences of ITS and nLSU of the studied samples were generated, and phylogenetic analysis was performed with Maximum Likelihood, Maximum Parsimony, and Bayesian Inference methods. The phylogenetic analysis indicated that the new species belongs to the genus Efibula and is grouped with the taxa E. daweishanensis, E. grandinosa, and E. shenghuae. A description, illustrations, and phylogenetic analysis results of the new species are provided. The discovery of this species not only contributes to the diversity of Efibula in subtropical Asia but also provides further clarification of its phylogenetic relationships.